Analysis of Judicial Considerations in the Case of Fake News Dissemination and Its Impact on Public Order - Hutauruk, Rufinus Hotmaulana; Sudirman, Lu; Julvina, Julvina (Nomos : Jurnal Penelitian Ilmu Hukum, 2025)
This research addresses the legal issues surrounding the dissemination of false news, particularly in the case of Decision Number 686/Pid.Sus/2021/PN JKT, which involves the spread of fabricated content on social media. The purpose of this study is to analyze judicial considerations in the legal handling of fake news and its implications on public order. The research employs a normative legal method, using secondary data from the court's decision and analyzing it through document analysis with a case-based and conceptual approach. The results highlight the court's focus on the intentionality of the defendants, their awareness of the false nature of the content, and the potential risks of public unrest. The study concludes that while media freedom is constitutionally protected, it must be exercised responsibly, especially in the digital age, to prevent harm to public order and societal harmony. This case underscores the need for greater media accountability and the balance between freedom of expression and public safety.